Evektivitas Dakwah Ustad Hanan Attaki Dalam Media Sosial Terhadap Spiritual Generasi Z - Iskandar, Isak; M, Melisa; Muhammad, Fadhil; Mardiyyah, Sayyidatul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the role of Ustadz Hanan Attaki's YouTube social media account and its effectiveness as a medium of preaching for the spiritual generation Z. The problem in this study is how effective is Ustad Hanan Ataki's preaching through social media in influencing spiritual changes in Gen Z through the YouTube account @HananAttaki. This study aims to determine the role of Ustadz Hanan Attaki's YouTube social media account in preaching and see its effectiveness. The method used in this study is a descriptive qualitative approach by taking YouTube social media. Data collection techniques are carried out through observation, interviews, and documentation. The sample in this study was taken by purposive sampling on followers of the @HananAttak account. The results of the study show that the role of Ustadz Hanan Attaki's YouTube account as a medium of preaching is quite good for followers because it can influence individual behavior in society such as getting information, insight and entertainment. The effectiveness of the preaching message through the YouTube account @HananAttaqi is very effective because it has entered the thoughts and feelings as well as actions or reactions of followers of the @HananAttak account who are considered passive and only receive the messages conveyed.